2014
DOI: 10.1002/2013jd021397
|View full text |Cite
|
Sign up to set email alerts
|

The influence of natural and anthropogenic factors on major stratospheric sudden warmings

Abstract: Major stratospheric sudden warmings are prominent disturbances of the Northern Hemisphere polar winter stratosphere. Understanding the factors controlling major warmings is required, since the associated circulation changes can propagate down into the troposphere and affect the surface climate, suggesting enhanced prediction skill when these processes are accurately represented in models. In this study we investigate how different natural and anthropogenic factors, namely, the quasi‐biennial oscillation (QBO),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 79 publications
(151 reference statements)
1
18
0
Order By: Relevance
“…One might also object that the forcing in the scenario used of our runs (RCP6.0) is not extreme enough to produce a significant signal in the frequency and duration of SSWs, but that a significant change would occur with stronger forcing, such as the RCP8.5 scenario. Although we cannot rule out this possibility, it seems improbable based on a similar lack of significance in the results documented for that very extreme scenario by several previous studies (Mitchell et al, 2012a;Ayarzagüena et al, 2013;Hansen et al, 2014;Kim et al, 2017). Nevertheless, it would be hard to verify the hypothesis because of the low number of CCMI RCP8.5 simulations available.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…One might also object that the forcing in the scenario used of our runs (RCP6.0) is not extreme enough to produce a significant signal in the frequency and duration of SSWs, but that a significant change would occur with stronger forcing, such as the RCP8.5 scenario. Although we cannot rule out this possibility, it seems improbable based on a similar lack of significance in the results documented for that very extreme scenario by several previous studies (Mitchell et al, 2012a;Ayarzagüena et al, 2013;Hansen et al, 2014;Kim et al, 2017). Nevertheless, it would be hard to verify the hypothesis because of the low number of CCMI RCP8.5 simulations available.…”
Section: Discussionmentioning
confidence: 60%
“…While Mahfouf et al (1994) found an increase in the frequency of SSWs under doubled-CO 2 conditions, Rind et al (1998) reported a decrease, and Butchart et al (2000) did not find any change that might be attributed to increasing GHG concentrations. And, in spite of an improved stratospheric representation and more realistic model features in the last decade, a clear consensus as to future SSW changes is still missing (Charlton-Perez et al, 2008;Bell et al, 2010;SPARC CCMVal, 2010;Mitchell et al, 2012a, b;Hansen et al, 2014;Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Different configurations of the same model can lead to different background circulation and thus to different atmospheric wave dynamics, which has been shown to impact not only the occurrence of stratospheric warming but also the atmospheric response to different forcings like, greenhouse gases (GHG), ENSO-and NAV-induced SST variability. The significant difference in stratospheric wave dynamics and even in the Major Stratospheric Warming (MSW) between ocean/atmosphere-coupled and standalone atmosphere configurations of the same model has been shown using the Community Earth System Model (CESM) (Hansen et al 2014). Similar differences in wave dynamics and circulation changes have been shown between configurations with and without Quasi-Biennial Oscillation (QBO) (Hansen et al 2014) and between high-top and low-top configurations in response to GHG (Karpechko and Manzini 2012), NAV Fig.…”
Section: Discussionmentioning
confidence: 66%
“…The significant difference in stratospheric wave dynamics and even in the Major Stratospheric Warming (MSW) between ocean/atmosphere-coupled and standalone atmosphere configurations of the same model has been shown using the Community Earth System Model (CESM) (Hansen et al 2014). Similar differences in wave dynamics and circulation changes have been shown between configurations with and without Quasi-Biennial Oscillation (QBO) (Hansen et al 2014) and between high-top and low-top configurations in response to GHG (Karpechko and Manzini 2012), NAV Fig. 9 Simulated stratospheric changes associated with large-scale Atlantic cooling conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The stratospheric polar vortex is also expected to change in the future as a result of long-term anthropogenic changes in atmospheric composition, that is, increasing greenhouse gas (GHG) concentrations and stratospheric ozone layer recovery. For instance, several studies have examined possible trends in the future occurrence of midwinter SSWs (e.g., Ayarzagüena et al, 2018;Bell et al, 2010;Hansen et al, 2014;Karpechko & Manzini, 2017;Kim et al, 2017;Manzini et al, 2014;Mitchell et al, 2012;SPARC CCMVal, 2010), but no consensus has been reached yet. Nevertheless, the effects of projected climate change on SFWs have not been addressed.…”
Section: Introductionmentioning
confidence: 99%